Comparative analysis of ascorbic acid in human milk and infant formula using varied milk delivery systems - Dickton Darby; Brewer Paul; Rogers Kristy; Francis Jimi; Pardini Ron (BMC, 2008)
Abstract Background The expression of human milk for later use is on the rise. Bottle systems are used to deliver the expressed milk. Research has shown that storage of both human milk and artificial baby milk, or infant formula, leads to a loss of ascorbic acid (commonly called Vitamin C). As milk is removed from the bottle during feeding and replaced by ambient air, it is unknown if loss of ascorbic acid occurs during the course of a feeding. The purpose of this study is to investigate the effect of the milk delivery system on levels of ascorbic acid in human milk and infant formula. The objectives are to 1) determine changes in ascorbic acid concentration during a 20 minute "feed," 2) determine if there is a difference in ascorbic acid concentration between delivery systems, and 3) evaluate if any differences are of clinical importance. Methods Commonly available bottles were used for comparison of bottle delivery systems. Mature human milk was standardized to 42 mg/L of ascorbic acid. Infant formula with iron and infant formula with docosahexanoic acid were used for the formula samples. Each sample was analyzed for ascorbic acid concentration at baseline (0), 5, 10, 15, and 20 minutes. Each collection of samples was completed in triplicate. Samples were analyzed for ascorbic acid using normal-phase high performance liquid chromatography. Results Ascorbic acid concentration declined in all bottle systems during testing, Differences between the bottle systems were noted. Ascorbic acid concentrations declined to less than 40% of recommended daily intake for infants in 4 of the bottles systems at the 20 minute sampling. Conclusion The bottle systems used in this study had measurable decreases in the mean concentration of ascorbic acid. More research is needed to determine if the observed decreases are related to lower plasma ascorbic acid concentration in infants exclusively bottle fed. The decrease of ascorbic acid concentration observed in both human milk and infant formula using varied milk delivery systems may be of clinical importance. For infants who rely solely on bottle feeds there may be increased risk of deficiency. Bottle shape, size, and venting should be considered.